Strengthening accountability for business in nutrition - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
The actions and activities of businesses have a profound effect on nutrition outcomes. Businesses—large, medium, and small enterprises that employ people for wages—produce goods and services that are critical determinants of nutrition, including food and beverages, drugs, water, and sanitation. Businesses employ the vast majority of people in the workforce, and their working conditions are important determinants of people’s overall health. Business actions also affect the environment, which can in turn shape nutrition outcomes.